Comportamento informacional de profissionais da área de Meteorologia do Brasil e de Portugal: um estudo exploratório - Santos, Fernando Bittencourt dos (2016)
This study intends, as a general goal, analyze the information behavior by two public institutions professional Meteorology area - the Instituto Nacional de Meteorologia (INMET), in Brazil, and Instituto Português do Mar e da Atmosfera (IPMA) in Portugal - in order to support the creation of an informational role model for the area. To achieve the overall objective, research has the following specific objectives: (A) describe the weather information, including its historical and current aspects and focusing on the context of Brazil and Portugal; (B) outline the informational profile of meteorologists of the two institutions mentioned above public; (C) identify the search habits and use as well as the meteorologists information needs and, finally, (D) identify the sources of information considered essential for these professionals. The research is characterized as the methodological aspects such as exploratory, of qualitative and quantitative approach, supported by the literature, and the subjects will be Meteorology professionals distributed between INMET and IPMA. Data collection will be done through the application of specific questionnaire and observation technique, both performed with the environments in which professionals work. As partial consideration, it is emphasized that the creation of the model proposed in this research, will only be optimized if the information needs, and hence the behavior of users mentioned above, are well defined.